Mechanical design for collaborative robot (CoBot) platform and autonomous mobile robot (AMR) - coupling and decoupling (II) - Chen, Xing Heng (Nanyang Technological University, 2023)
Mechanical design is a field of engineering that involves the application of principles of physics, mathematics, and material science to the design and development of mechanical systems. It encompasses a wide range of disciplines, including product design, machine design and structural design. The author utilized design thinking and mechanical skills including computer-aided design (CAD) software, simulation tools (ANSYS) to produce suitable power sharing mechanisms between Dual Extendable, the Autonomous Mobile Robot (AMR) DEX and Collaborative robot platform. This paper covers investigation and analysis of current power sharing mechanisms including different types of connectors, providing valuable insights into the efficiency, safety, and interoperability of power transfer systems. Author then makes informed decisions when designing power sharing mechanism that is optimized for this specific AMR-CoBot system application. In this project, design and development of the power sharing mechanism will be explained in detail, and various assessments will be done to determine the performance of the mechanism. Further improvements that could be useful in increasing efficiency and of the system will be discussed at last.